Strategi Komunikasi dalam Penanganan Polemik LCC 4 Pilar Kalimantan Barat: Perspektif Two-Way Symmetrical Communication - Nur Atikah Taang; Suryani Musi; Vika Oktasya; Nia Ramadani; Dwi Reskita Nur Atikah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The controversy surrounding the Four Pillars Quiz Competition (Lomba Cerdas Cermat/LCC) organized by the Indonesian People’s Consultative Assembly (MPR RI) in West Kalimantan attracted public attention after participants questioned inconsistencies in the scoring process during the final round. The issue developed into public discourse on social media and raised concerns regarding the transparency of institutional communication in managing the conflict. This study aims to analyze institutional communication strategies in addressing the controversy through the perspective of Two-Way Symmetrical Communication. Using a qualitative library research approach, data were collected from scholarly articles, online news, institutional documents, and relevant literature on organizational communication, crisis communication, and Two-Way Symmetrical Communication. The findings show that the organizers demonstrated dialogue, feedback acceptance, and institutional adaptation; however, these practices remained partial. Communication adaptation became evident after the conflict escalated through evaluations, suspension of related parties, and public apologies, emphasizing the importance of responsive and dialogic communication strategies.